Relationships Among Cognitive Function, Frailty, and Health Outcome in Community-Dwelling Older Adults - Xue, Huiping; Huang, Chunxia; Zhu, Qin; Zhou, Shuixin; Ji, Yunlan; Ding, Xiaohui; Zhang, Dandan; Gu, Dongmei (Frontiers in Aging Neuroscience, 2022)
Background Frailty and cognitive impairment are significant problems faced by older adults, which have a significant impact on their activities of daily living, social activities, and quality of life. Design Cross-sectional study. Methods A total of 252 older adults in two communities in Yangzhou were randomly selected. The cognitive function of the elderly was assessed using the Memory and Executive Screening (MES). The frailty phenotype was used to evaluate the frail situation of older adults. The activity of daily living (ADL), functional activities questionnaire (FAQ), and European quality of 5-dimensions (EQ-5D) were used to evaluate health outcomes in the elderly. SEM was used to explore the direct and indirect relationship among cognitive function, frailty and health outcomes. Results There was a significant direct correlation between cognitive function and frailty; the direct effect was −0.521. The influence path of cognitive function on health outcomes included direct and indirect effects; the total effect was −0.759. The effect of frailty on health outcomes included direct and indirect effects; the total effect was 0.440. Conclusion According to SEM, cognitive function interacts with frailty and may reduce the quality of life, the ADL, and social activities among older adults directly and indirectly, so future assessments of older adults should consider both cognitive function and frailty, so as to further improve the health outcome of the elderly. When formulating relevant intervention measures in the future, we need to consider that it cannot only improve the cognitive function, but also improve the frail situation, so as to jointly improve the health outcomes of older adults.